"X" Marks the Spot: An Injection Technique for Alopecia Areata. Issue 2 (10th March 2017) - Agrawal, Shruti; Patel, Devika; Shwayder, Tor
Abstract: Children with alopecia areata often have multiple patches of hair loss. When administering intralesional steroid injections, it can be difficult to monitor which areas have already been treated. Additionally, patients and their parents may worry that we did not treat all of the affected areas. We describe a simple technique to keep track of which areas have been treated.